ETIOLOGICAL SPECTRUM OF OBSTRUCTIVE JAUNDICE - Khanzada, Tariq Wahab; Samad, Abdul; Memon, Waseem; Kumar, Basant (Journal of Postgraduate Medical Institute, 2011)
Objective: The objective of this study was to determine the etiological spectrum of obstructive jaundice in this part of the world. Material and Methods: This prospective study was carried out at Liaquat National Hospital, Karachi from March 1997 to February 2001 and later at Isra University Hospital, Hyderabad from January 2003 to December 2006. Sixty five patients with obstructive jaundice were included in this study. The data was collected with respect to patient's identity, age, gender and cause of the obstructive jaundice. Results: Fifty seven percent of patient had malignant obstructive jaundice and carcinoma of head of pancreas being the leading cause of malignant obstructive jaundice. Forty three percent patients had benign causes of obstructive jaundice, choledocholithiasis being the most common benign cause. Conclusion: Choledocholithiasis and malignancy are the two major causes of obstructive jaundice.